Anomalous increase of sub-band gap photoluminescence from InPBi layers grown by liquid phase epitaxy. (3rd May 2019) - Bhowal, M K; Das, Subhasis; Sharma, A S; Das, S C; Dhar, S
Abstract: The luminescence properties of InPBi layers, grown by liquid phase epitaxy from an In-P melt containing 4 and 18 wt% Bi are investigated. As-grown layers, as well as layers subjected to a high temperature anneal, are studied by atomic force microscopy (AFM), energy dispersive x rays (EDX), high resolution x ray diffraction (HRXRD) and low temperature photoluminescence (PL) spectroscopy. AFM shows formation of microscopic granular structure over the surface of the layer grown from melt containing 18 wt% Bi after a high temperature furnace anneal at 700 °C for 1 h. Lattice contraction and a decrease of Bi content is observed for both kinds of samples after anneal though it is only marginal in case of the layer grown from melt containing 4 wt% Bi but quite appreciable in case of the other sample. From EDX and XRD results, the observed decrease in Bi content as a result of high temperature anneal is suggested to be due to diffusion of Bi atoms from the layer to InP grains formed over the layer surface. 10 K PL measurements showed the expected band edge luminescence peak at 1.38 eV. A second peak at 1.33–1.34 eV is observed which shows a large post anneal enhancement for materials grown from melts containing higher amounts of Bi. It is suggested that this peak is due to luminescence from defects formed by complexes of Bi with phosphorous vacancies. Photoluminescence also revealed a broad peak between 1–1.22 eV whose intensity increased anomalously with temperature up to 104 K. The anomalous increase up to 28 K is found to be associated with a low activation energy of 0.35 meV and is speculated to be due to the transfer of holes in the localized states to the valence band. Above 28 K, PL increases with an activation energy of 9.66 meV and may be explained on the basis of similar observation made by a previous group [Chen et al Appl. Phys. Lett. 110, 051 903 (2017)] who explained the phenomenon by assuming thermal hopping of some electrons available for recombination with holes to some non-radiative states .